2012
DOI: 10.1021/jp210455w
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Si/CdS Radial Nanowire Heterojunction Photodetectors Using Etched Si Nanowire Templates

Abstract: p-Si/n-CdS radial heterojunction nanowires have been grown by pulse laser deposition of CdS on vertically aligned Si nanowires fabricated using a room temperature wafer-scale etching of p-type Si. Temperature-dependent photoluminescence characteristics have been studied in detail in the blue−green−red regions from these p-Si/n-CdS core−shell nanowires. The photocurrent spectra of the nanowire heterojunctions have been investigated at room temperature to study the spectral responsivity and detectivity of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 32 publications
6
80
0
Order By: Relevance
“…This achieved R value is larger than that of a commercial Si photodiode PD (in the range 0.1À0.2 A/W at 442 nm), 27 near 100 times larger in magnitude than that obtained from a Si/ZnO coreÀshell NW array PD (1.0 Â 10 À2 A/W, 480 nm, À1 V), 28 also larger than that of a Si/CdS coreÀshell NW network PD (<1 A/W, 480 nm, À1 V). 29 To illustrate the piezo-phototronics effect on photoresponsivity more clearly, relative changes of photoresponsivity R with respect to R 0 (corresponding photoresponsivity at no strain) are calculated and summarized in Figure 4d. It is observed that, under each power density, the relative change of R varyies with applied strain in a similar manner to that of photocurrent ΔI (Figure 4b) and photoreponsivity R (Figure 4c), displaying a maximum value at an external strain of À0.10%.…”
Section: Resultsmentioning
confidence: 99%
“…This achieved R value is larger than that of a commercial Si photodiode PD (in the range 0.1À0.2 A/W at 442 nm), 27 near 100 times larger in magnitude than that obtained from a Si/ZnO coreÀshell NW array PD (1.0 Â 10 À2 A/W, 480 nm, À1 V), 28 also larger than that of a Si/CdS coreÀshell NW network PD (<1 A/W, 480 nm, À1 V). 29 To illustrate the piezo-phototronics effect on photoresponsivity more clearly, relative changes of photoresponsivity R with respect to R 0 (corresponding photoresponsivity at no strain) are calculated and summarized in Figure 4d. It is observed that, under each power density, the relative change of R varyies with applied strain in a similar manner to that of photocurrent ΔI (Figure 4b) and photoreponsivity R (Figure 4c), displaying a maximum value at an external strain of À0.10%.…”
Section: Resultsmentioning
confidence: 99%
“…One-dimensional (1D) semiconducting heterostructures [8][9][10][11] are considered the most promising sensitive photodetection materials because they offer not only the high photoconductive gain and property benefits of 1D nanostructures (rich surface trap states and large surface-to-volume ratio) but also the added benefit of multifunctions or new properties arising from the synergistic effects of combining heterojunction materials. Furthermore, the formed heterojunction interface can greatly enhance these PDs' detectivity, response speed, and responsivity [12][13][14][15][16][17]. Fang's group reported that PDs based on both ZnS/ZnO [18] and GaP/ZnS [19] 1D heterojunctions exhibited improved light-detection properties such as a high photoresponsiveness and high spectral selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…6−10 Second, III−V and II−VI NWs have been grown vertically on Si and germanium substrates 11−27 and on Si NWs, forming branched heterostructure NWs. 28 Lastly, there has been recent interest in core/ shell heterostructure NWs, though the Si/III−V or II−VI core/ shell interfaces are often difficult to control 29 or have not been characterized 30 and shells of high crystal quality with thicknesses beyond several nanometers have not been explored. 6,31,32 Conceptually, facet-selective growth provides a means by which to reduce the interfacial area of mismatched materials since the growing layer is confined to the width of the facet on which it is deposited.…”
mentioning
confidence: 99%